Validation study of the Mini-Mental State Examination in a Malay-speaking elderly population in Malaysia - M. Ibrahim, Norlinah; Shohaimi, Shamarina; Heng-Thay, Chong; Abdul Rahman, Abdul Hamid; Razali, Rosdinom; Ebernezer, Esther; B. Basri, Hamidon (Karger, 2009)
Background/Aims: In view of the differing sensitivity and specificity of the Mini-Mental State Examination (MMSE) in the non-English-speaking populations, we conducted the first validation study of the Malay version (M-MMSE) in Malaysia among 300 subjects (from the community and outpatient clinics).